Remarkable Conductivity of a Self-Healing Single-Ion Conducting Polymer Electrolyte, Poly (ethylene-co-acrylic lithium (fluoro sulfonyl)imide), for All-Solid-State Li-Ion Batteries - Ahmed, Faiz; Choi, Inhwan; Rahman, Md Mahbubur; Jang, Hohyoun; Ryu, Taewook; Yoon, Sujin; Jin, Lei; Jin, Yongcheng; Kim, Whangi (ACS applied materials & interfaces, 2019)
Single-ion conducting polymer electrolyte (SICPE) is a safer alternative to the conventional high-performance liquid electrolyte for Li-ion batteries. The performance of SICPEs based Li-ion batteries is limited due to the low Li conductivities of SICPEs at room temperature. Herein, we demonstrated the synthesis of a novel SICPE, poly (ethylene-co-acrylic lithium (fluoro sulfonyl)imide) (PEALiFSI) with acrylic (fluoro sulfonyl)imide) anion (AFSI). The solvent and plasticizer-free PEALiFSI electrolyte, which was assembled at 90 °C under pressure, exhibited self-healing properties with remarkably high Li conductivity (5.84×10 S/cm at 25 °C). This is mainly due to the self-healing behavior of this electrolyte, which induced to increase the proportion of the amorphous phase. Additionally, the weak interaction of Li with the resonance stabilized AFSI anion is also responsible for high Li conductivity. This self-healed SICPE showed high Li transference number (ca. 0.91), flame and heat retardancy, and good thermal stability, which concurrently delivered ca. 88.25% (150 mAh/g at 0.1 C) of the theoretical capacitance of LiFePO cathode material at 25 °C with the full cell configuration of LiFePO /PEALiFSI/graphite. Furthermore, the self-healed PEALiFSI based all-solid-state Li-battery showed high electrochemical cycling stability with the capacity retention of 95% after 500 charge-discharge cycles.